The Influence of Safety Leadership, Safety Motivation, and Working Condition on Safety Behavior at PT XYZ - Narendra, Made Diksi; Dudija, Nidya (Jurnal Manajemen Indonesia, 2024)
Coal mining industry is an industry that can be classified as a high-risk industry. Work accident in this industry can happen to all workers any time. PT XYZ, as a company that provides contractor services in coal mining industry, also records work accident in its workplace. This research aims to determine and analyze the influence of safety leadership, safety motivation, and working condition on safety behavior at PT XYZ. To achieve this goal, measurements will be conduct to measure the dimension from each variable. The method that will be used in this research to achieve this goal is to develop and test a structural equation modelling (SEM) on a questionnaire that has been distributed to samples from the population. The research sample consisted of 262 operators who worked in Production Department PT XYZ. The findings showed that safety leadership and working condition have a positive and significant effect on safety behavior. Meanwhile, the result also showed that safety motivation did not have a significant effect on safety behavior in PT XYZ. The results of this study provide an overview of the real conditions currently occurred in PT XYZ. The findings also provide guidance for leaders in the coal mining industry on the behaviors and policies they should adopt to improve safety-related performance.